PERSEPSI MAHASISWA TERHADAP SIKAP MAHASISWA PADA PEMBELAJARAN DOKKAI MENGGUNAKAN ZOOM CLOUD MEETING - Yulia Ranti Fajri; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine student perceptions of student attitudes in the implementation of dokkai using zoom cloud meetings. This study uses a quantitative descriptive approach. The study population was all students of Japanese Language Education FKIP Riau University Class of 2019 with a research sample of 34 people. The data analysis technique used a 5-point Likert scale. From the results of the research using a questionnaire, it was found that the indicators of student attitudes in the implementation of dokkai categorized as quite positive interpretations because they were at the interval limit of 2.61-3.40. For indicators of student attitudes, there are 5 statement items regarding student ethics, when student lectures come on, a conducive learning environment, students prepare before lectures, and student responses when the lecturer asks.Key Word: Perception, Student Attitude, Dokkai Learning